'Things may look normal': representing absence in Oulipian literature - Landy, Patrick (2022)
The critical component of this thesis explores the representation of absence in the constraint-based literary works of the Oulipo. While some critics have misconstrued Oulipian writing as overly reliant on chance or incapable of addressing serious themes, a closer examination of the group’s endeavours suggests otherwise. Despite being governed by strict mathematical or linguistic constraints, Oulipian texts invite us to explore the intricate and often profoundly personal worlds they have constructed, touching upon a wide range of social, historical, and autobiographical issues. In this respect, a central theme that unites a considerable number of Oulipian texts is absence, which in the context of Oulipian poetics tends to be rooted in grief, memory, and the passing of time. Given the Oulipo’s preoccupation with potential, the prominence of absence in Oulipian literature raises questions as to why constraint-based texts gravitate towards representing absence. Using Marcel Bénabou’s classifications of constraint visibility as a framework, this thesis examines the relationship between constraint and absence in five Oulipian texts. Chapter one explores the role of absence in Jacques Roubaud’s Some Thing Black, a collection of poems whose numerical structure serves as a foundation for Roubaud to mourn the loss of his wife. Chapter two investigates how the absence of gender in Anne Garréta’s novel Sphinx impacts the narrator’s experience of love, identity, and desire for annihilation. Chapter three addresses Italo Calvino’s Invisible Cities, whose mathematical structure gives shape to the absence of the city and the self. Chapter four explores how the absence of the letter ‘e’ in Georges Perec’s lipogrammatic novel A Void manifests itself in the text and pertains to the loss of Perec’s family in the Holocaust. Chapter five examines Inger Christensen’s poem alphabet, which explores the impact of nuclear devastation upon the environment while being governed by a mathematical constraint based on the Fibonacci sequence and a linguistic constraint that revolves around the alphabet. Given the inclusion of Christensen, who was not a member of the Oulipo, I consider how the Oulipian approach can extend beyond the group itself and be used by any writer to address absence as they see fit. Furthermore, I make the case that the Oulipian approach gravitates towards absence due to the writer’s ability to address subjects they would not have been able to without the use of constraints, which give rise to freedom and catharsis in the writing process.